2012
DOI: 10.1186/1475-2840-11-79
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hyperglycemia and endothelial function in type 2 diabetes: focus on mitiglinide

Abstract: The risk of cardiovascular complication in a diabetes patient is similar to that in a nondiabetic patient with a history of myocardial infarction. Although intensive control of glycemia achieved by conventional antidiabetic agents decreases microvascular complications such as retinopathy and nephropathy, no marked effect has been reported on macrovascular complications or all-cause mortality. Evidence from VADT, ACCORD, and ADVANCE would suggest that glycemic control has little effect on macrovascular outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 101 publications
(101 reference statements)
0
26
0
1
Order By: Relevance
“…In addition, the management of postprandial hyperglycemia in type 2 diabetes is related to regression of atherosclerosis [30]. For example, Mitiglinide, a short-acting insulinotropic agent to ameliorate postprandial hyperglycemia, was shown to reduce excess oxidative stress and inflammation [31]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the management of postprandial hyperglycemia in type 2 diabetes is related to regression of atherosclerosis [30]. For example, Mitiglinide, a short-acting insulinotropic agent to ameliorate postprandial hyperglycemia, was shown to reduce excess oxidative stress and inflammation [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Results of the STOP-NIDDM trial, which showed that α-GIs reduce the incidence of cardiovascular events even in patients with impaired glucose tolerance, suggest the clinical importance of interfering with postprandial changes in glucose [19]. Thus, because repetitive PPHG is thought to cause cardiovascular events [46,48], ameliorating PPHG may affect endothelial function and prevent cardiovascular events [22,38,46]. In the present study, we observed a significant inverse correlation between postprandial endothelial function and PPHG.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in carotid intima-media thickness was associated with the improvement of postprandial. Therefore, treating postprandial hyperglycemia may have a positive effect on atherosclerosis progression and cardiovascular diseases (Kitasato et al 2012).…”
Section: Discussionmentioning
confidence: 99%